Focus the hidden driver of excellence - Goleman, Daniel (New York Harper, 2014)
For more than two decades, psychologist and journalist Daniel Goleman has been scouting the leading edge of the human sciences for what's new, surprising, and important. In Focus, he delves into the science of attention in all its varieties, presenting a long overdue discussion of this little-noticed and under-rated mental asset that matters enormously for how we navigate life.
Includes bibliographical references (pages 261-265) and index.
Keywords: Attention